Impulsive differential inclusions involving evolution operators in separable Banach spaces - Benchohra, M.; Nieto, J.J.; Ouahab, A. (Український математичний журнал, 2012)
We present some results on the existence of mild solutions and study the topological structures of the sets of solutions for the following first-order impulsive semilinear differential inclusions with initial and boundary conditions:
where J=R+, 0 = t 0 < t 1 < … < t m <…, m∈N, lim k→∞ t k = ∞, A(t) is the infinitesimal generator of a family of evolution operators U(t, s) in a separable Banach space E and F is a set-valued mapping. The functions I k characterize the jumps of solutions at the impulse points t k , k = 1, ….The mapping L: PC b →E is a bounded linear operator. We also investigate the compactness of the set of solutions, some regularity properties of the operator solutions, and the absolute retract. Наведено деякi результати про iснування м’яких розв’язкiв та вивчено топологiчну будову множин розв’язкiв для наступних iмпульсних напiвлiнiйних диференцiальних включень першого порядку з початковими та граничними умовами:
де J=IR+,0=t0<t1<...<tm<...;(m∈N),limk→∞tk=∞,A(t) — iнфiнiтезимальний генератор сiм’ї операторiв еволюцiї U(t,s) на сепарабельному банаховому просторi E та F — багатозначне вiдображення. Функцiї Ik характеризують стрибки розв’язкiв в точках iмпульсної дiї tk,k=1,... . Вiдображення L:PCb→E є обмеженим лiнiйним оператором. Також дослiджено компактнiсть множини розв’язкiв, деякi властивостi регулярностi операторних розв’язкiв та абсолютну ретрактнiсть.